Kultivasi Citra Kepolisian di Media Sosial - Izzul Hudia Alfaza; Prahastiwi Utari (Universitas Sebelas Maret (UNS), 2024)
The @txtdrberseragam Twitter account is a Twitter account that contains a variety of news, complaints, and frustrations about uniformed officers, including the police. Researcher found that this account may be influencing the public's perception of the police. This study aims to determine the cultivation process that occurs in the @txtdrberseragam Twitter account against the image of the police in society. The researcher is interested in conducting this research because social media has now become a staple for society, so it can influence the way people think, perceive, and behave. This study was conducted using a mixed method (mixed) with content analysis techniques and in-depth interviews with a number of informants. A total of 68 contents (tweets and retweets) of the @txtdrberseragam account posted from June 1 to 29, 2023 were taken as samples for analysis. Next, 11 followers of the account were selected using purposive sampling to be interviewed as informants. The researcher used the constructivism paradigm to seek out the possible realities that exist and understand how the process of someone's interpretation of something works. The result of the study is the fact that a subjective reality is formed in the eyes of the public who view the police as a bad figure. The existence of the @txtdrberseragam Twitter account directly influences public perception through the media exposure that occurs. In addition, there are other factors such as personal experience, the credibility of the information source, which also contribute to the formation of the existing subybjective reality.